2018
DOI: 10.18002/cg.v0i13.5402
|View full text |Cite
|
Sign up to set email alerts
|

Segregación laboral, el caso de las Ingenieras Mecánicas Electricistas = Labor segregation: the case of female Electrical Mechanical Engineers

Abstract: ResumenLa presencia de la mujer en el ámbito laboral es mayor cada día, sin embargo, los roles y estereotipos de género que prevalecen en nuestra sociedad dificultan su desarrollo profesional, por ejemplo, en la ingeniería, profesión considerada masculina. El presente estudio es de corte cualitativo. Las participantes clave son Ingenieras Mecánicas Electricistas (IMEs) egresadas de la Universidad Autónoma de San Luis Potosí (UASLP). Los resultados muestran que las participantes son asignadas en espacios como l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…However, women's insertion in new public spaces, such as the workplace, has not exempted them from reproducing the gender patterns imposed (Martínez Méndez, 2018 ). That is why gender equality should form an essential part of corporate culture even if evidence has shown that in most cases, legislative tools are needed to force companies to adapt their corporate values and intensify their strategies against gender discrimination.…”
Section: Corporate Culture and Gender Equalitymentioning
confidence: 99%
“…However, women's insertion in new public spaces, such as the workplace, has not exempted them from reproducing the gender patterns imposed (Martínez Méndez, 2018 ). That is why gender equality should form an essential part of corporate culture even if evidence has shown that in most cases, legislative tools are needed to force companies to adapt their corporate values and intensify their strategies against gender discrimination.…”
Section: Corporate Culture and Gender Equalitymentioning
confidence: 99%